Capital Structure, CSR Disclosure, and Firm Value: The Moderating Role of Profitability - Fadilla Rezky Hendrani; Anita Ade Rahma; Ronni Andri Wijaya (GOVERNORS, 2026)
Firm value reflects investors’ assessment of a company’s financial prospects, risk, and long-term value creation. This study examines the effects of capital structure and corporate social responsibility (CSR) disclosure on firm value and investigates whether profitability moderates these relationships. Using a quantitative explanatory design, the study analyzes secondary data from 21 firms listed on the Indonesia Stock Exchange during 2022–2024, resulting in 63 observations. Firm value is measured by Price-to-Book Value (PBV), capital structure by Debt-to-Equity Ratio (DER), CSR disclosure by an index based on the Global Reporting Initiative (GRI) Standards 2021, and profitability by Return on Assets (ROA). Fixed-effects panel regression with interaction terms is employed to test the direct and moderating relationships. The results show that capital structure has a positive and statistically significant relationship with firm value, indicating that higher leverage is associated with higher market valuation within the observed sample. In contrast, CSR disclosure has no statistically significant relationship with firm value, suggesting that disclosure breadth alone does not sufficiently explain variation in market valuation. Profitability also does not significantly moderate either the capital structure–firm value relationship or the CSR disclosure–firm value relationship. Overall, the findings indicate an asymmetric valuation pattern in which capital structure is more strongly associated with firm value than CSR disclosure, while profitability does not function as a significant contingency variable for either relationship. The study contributes to the literature by providing recent evidence from the Indonesian capital market on the differentiated valuation relevance of financial leverage and CSR disclosure.